Dr. carbles is losing his marbles! eaudiobook - Gutman, Dan (My Weird School, 2015)
Forget Thanksgiving. The biggest turkey of all is running around Ella Mentry School—Dr. Carbles, the president of the school board. He is grumpier than ever and wants to fire Mr. Klutz. Will A.J. and his friends be able to save their principals job?